PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KELURAHAN DI WILAYAH KECAMATAN KEPANJEN KABUPATEN MALANG - Nazil, Fina Izmi; Respati, Harianto; Natsir, Mokhamad (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2024)
This study aims: (1)To describe the variables of work motivation, work discipline, job satisfaction and employee performance at the village office in the Kepanjen District area; (2)To determine and analyze the effect of work motivation, work discipline, job satisfaction on employee performance at the village office in the Kepanjen District area; (3)To determine and analyze which of work motivation, work discipline, and job satisfaction has a dominant effect on employee performance at the village office in the Kepanjen District area. This research data uses primary data obtained from the results of distributing questionnaires using Likert scale research instruments. The questionnaire was distributed using the census method to all employees of the village office in the Kepanjen District of Malang Regency with a sample of 36 respondents. Data analysis techniques using descriptive analysis, multiple linear regression analysis, classical assumption test, t test and f test. The results of data analysis show that work motivation, work discipline, job satisfaction have a positive and significant effect on employee performance. Furthermore, it was found that work motivation has the most dominant influence on employee performance compared to work discipline and job satisfaction variables